An overview of illegal parrot trade in Maluku and North Maluku Provinces - Setiyani, Ayu Diyah; Ahmadi, Mukhtar Amin (Forest and Society, 2020)
Maluku is widely considered as a global avifauna hotspot. However, illegal parrot trades threatens numerous species to extinction. To date, there is no study on the extent of illegal trade in Maluku, which as a result, hampers efforts at targeting conservation initiatives. The aims of this study are to identify the pattern of illegal parrot trade, to identify factors that contribute to illegal parrot trade, and to identify actors involved in illegal parrot trade in Maluku and North Maluku Provinces. The study found that the number of wildlife rescued in 2018 was 1,402 individuals. Surprisingly, 84% (1,177 individuals) of the rescued wildlife were birds and approximately 96% (1,135 individuals) of the birds were parrots. Furthermore, the most commonly rescued parrots (90%) were from illegal trade seizures, and the remainder were handed over voluntarily by local communities. These trends indicate that the traffic of illegal parrot trade is extremely high. Meanwhile, the small number of handovers for birds indicates that there is an insufficient understanding and awareness among locals about wildlife laws and ecological values. The study identified three factors contributing to illegal parrot trade, which are the high potential for obtaining parrots with exotic appearances; the economic value of wild-caught parrots; and overall accessibility. The characteristics of the trade involved actors that can be defined as subsistence and opportunist harvesters, that work with several intermediaries, and consumers demand for pets. To overcome these challenges, there are two strategies which are proposed based on this research: (1) expand the upstream strategy focusing on protecting parrots in their habitats and empowering local communities to be involved in conservation; and (2) engage more on downstream strategies of emphasizing law enforcement and raising awareness.